(untitled) (Journal of Business and Technology (Dhaka), 2013)
Princeton University Press New Jersey, USA, 2011 ISBN: 9781400836017 DOI: http://dx.doi.org/10.3329/jbt.v6i2.14517 Journal of Business and Technology (Dhaka) VolVI, Issue02, (July-December, 2011) & VolVII, Issue-1 (January-June, 2012) pp.53-54